MAGNITUDES, SPATIAL SCALES AND PROCESSES OF ENVIRONMENTAL ANTIMONY MOBILITY FROM OROGENIC GOLD–ANTIMONY MINERAL DEPOSITS, AUSTRALASIA - Ashley P.M.; Craw D.; Tighe M.K.; Wilson N.J. (My University, 2006)
Antimony (Sb) is strongly concentrated into hydrothermal mineral deposits, commonly with gold, in metasedimentary sequences around the Pacific Rim. These deposits represent potential point sources for Sb in the downstream environment, particularly when mines are developed. This study documents the magnitude and scale of Sb mobility near some mineral deposits in Australia and New Zealand. Two examples of New Zealand historic mining areas demonstrate that natural groundwater dissolution of Sb from mineral deposits dominates the Sb load in drainage waters, with Sb concentrations between 3 and 24 μg/L in major streams. Mine-related discharges can exceed 200 μg/L Sb, but volumes are small. Sb flux in principal stream waters is ca 1–14 mg/s, compared to mine tunnel fluxes of ca 0.001 mg/s. Dissolved Sb is strongly attenuated near some mine tunnels by adsorption on to iron oxyhydroxide precipitates. Similar Sb mobilisation and attenuation processes are occurring downstream of the historic/active Hillgrove antimony–gold mine of New South Wales, Australia, but historic discharges of Sb-bearing debris has resulted in elevated Sb levels in stream sediments (ca 10–100+ mg/kg) and riparian plants (up to 100 mg/kg) for ca 300 km downstream. Dissolution of Sb from these sediments ensures that river waters have elevated Sb (ca 10–1,000 μg/L) over that distance. Total Sb flux reaching the Pacific Ocean from the Hillgrove area is ca 8 tonnes/year, of which 7 tonnes/year is particulate and 1 tonne/year is dissolved.
Keywords: ANTIMONY; MINE; RIVER; ENVIRONMENTAL CONTAMINATION; NEW ZEALAND; AUSTRALIA